Patterns of Systemic Hypertension among Adults with Perinatally Acquired HIV. (January 2017) - Ryscavage, Patrick; Macharia, Thomas; Trinidad, Lino R.; Lovelace, Susan; Tepper, Vicki; Redfield, Robert
Patients with perinatally acquired HIV may be at risk for the development of age-related non-AIDS diseases. The primary aim of this study was to describe patterns of systemic hypertension among a cohort of adults (≥18 years) with perinatally acquired HIV. A retrospective cohort study was conducted among adults (≥18 years) with perinatally acquired HIV infection. Primary outcomes included documentation of systemic hypertension as well as several additional non-AIDS-associated illnesses. Systemic hypertension incidence rates and rate ratios (RRs) were calculated among groups aged ≥18 and <18 years at the time of hypertension diagnosis. The overall prevalence of hypertension in the cohort (N = 109) was 26.6%, and the incidence rate of hypertension was significantly higher among those aged ≥18 years compared to those who are aged <18 years at the time of diagnosis (RR: 10.0, CI: 7.29-13.71). By multivariable analysis, only coexisting renal disease was associated with an increased risk of hypertension diagnosis.